Epidemiological profile of age-related macular degeneration patients in Federal University of Parana, Brazil - Pradella,Fernando Morandini (2016)
ABSTRACT Objective: To evaluate the profile and severity of age-related macular degeneration (AMD) in ophthalmology ambulatory of Federal University of Parana in Curitiba, Parana, Brazil. Methods: This was a cross-sectional study with data collected among the 6155 outpatients ophthalmic appointments (november 2011 to november 2013). In this 6155 patients, a total of 346 patients had retinal diseases and were screened by two retinal specialists for signs of AMD. If present, they were submitted to a protocol including a new ophthalmic evaluation comprising visual acuity, tonometry, biomicroscopy, dilated fundus examination and optical coherence tomography (OCT). Results: A total of 6155 patients underwent ophthalmologic evaluation for several reasons. Three hundred and forty six patients had retinal diseases (incidence of 5.6%) and 68 of these (incidence of 19.6% in retinal patients) had AMD. The mean age of all patients was 53 years and in retinal patients was 60 years. In AMD patients mean age was 73 years. Ethnicity, body-mass index (BMI) and smoking habits were evaluated in the 68 patients diagnosed with AMD (34 exudative and 34 non-exudative) but none of those parameters were statistically significant comparing exudative and non-exudative forms. Conclusion: Most of the patients were European descendants. A higher proportion of advanced cases of AMD comparing with literature was found (50% of exudative form). Regarding ethnicity, iris color, smoking habit and BMI, there was no difference comparing exudative and non-exudative forms. These results may be compared to available AMD studies, since there is little information about AMD in Brazil.